Fn-EDA (Fibronectin Containing Extra Domain A) in the Plasma, but Not Endothelial Cells, Exacerbates Stroke Outcome by Promoting Thrombo-Inflammation. Issue 5 (May 2019) - Dhanesha, Nirav; Chorawala, Mehul R.; Jain, Manish; Bhalla, Abhinav; Thedens, Daniel; Nayak, Manasa; Doddapattar, Prakash; Chauhan, Anil K.
Abstract : Background and Purpose—: Cellular Fn-EDA (fibronectin containing extra domain A) is expressed in activated endothelial cells and elevated in circulation in patients with cardiovascular diseases. Although global deficiency of Fn-EDA in mice improves stroke outcome, the specific contribution of plasma versus endothelium Fn-EDA in stroke outcome is currently unknown. We investigated the role of plasma versus endothelial Fn-EDA in stroke exacerbation in the comorbid condition of hyperlipidemia. Methods—: We generated novel plasma Fn-EDA −/− ( Fn-EDA fl/fl Alb Cre ) and endothelial Fn-EDA −/− ( Fn-EDA fl/fl Tie2 Cre ) strains on hyperlipidemic apolipoprotein E-deficient ( ApoE −/− ) background. By following the Stroke Therapy Academic Industry Roundtable guidelines, we evaluated stroke outcome in male and female mice. Susceptibility to ischemia/reperfusion injury was evaluated in 2 different models of stroke: intraluminal monofilament and embolic model on days 1, 3, and 7. Quantitative assessment of stroke outcome was evaluated by measuring infarct volume (by magnetic resonance imaging), cerebral blood flow (by laser speckle imaging), neurological and sensory-motor outcome, and postischemic thrombo-inflammation (platelet thrombi, fibrin, neutrophil, phospho-NFκB [nuclear factor κB], TNFα [tumor necrosis factor α], and IL1β [interleukin 1β]). Results—: Stroke outcome was comparable in ApoE −/− Fn-EDA fl/fl Tie2 Cre and control ApoE −/− Fn-EDA fl/fl mice suggesting endothelial Fn-EDA does not contribute to stroke. ApoE −/− Fn-EDA fl/fl Alb Cre mice exhibited significantly smaller infarcts and improved neurological and sensory-motor outcome at days 1, 3, and 7 in monofilament and embolic models of stroke. Improved stroke outcome was concomitant with enhanced survival, and decreased postischemic thrombo-inflammatory response ( P <0.05 versus ApoE −/− Fn-EDA fl/fl ). No sex-based differences were observed. Laser speckle imaging revealed significantly improved regional cerebral blood flow at 1 hour in ApoE −/− Fn-EDA fl/fl Alb Cre mice suggesting plasma Fn-EDA promotes postischemic secondary thrombosis. Coinfusion of anti–Fn-EDA antibody with r-tPA (recombinant tissue-type plasminogen activator) in ApoE −/− mice, 1 hour after embolization, improved stroke outcome with enhanced survival, and improved neurological outcome ( P <0.05 versus r-tPA). Conclusions—: Genetic evidence suggests that plasma Fn-EDA exacerbates stroke outcome by promoting postischemic thrombo-inflammation. Interventions targeting plasma Fn-EDA may reduce brain damage after reperfusion. Abstract : Supplemental Digital Content is available in the text.